A Landscape of Ethics in Research-Based Theater: Staging Lives of Family Members Who Have Passed. (February 2023) - Lea, Graham W.; Belliveau, George
Blending academic and theatrical worlds in research-based theater (RbT) requires balancing academic demands of institutionalized research and aesthetic demands of theater. This duality becomes particularly significant regarding ethics. With so much possibility, it becomes imperative for practitioners to share, and learn from, vulnerable and challenging ethical experiences. This creates landscapes of ethical possibilities for RbT and guideposts for navigating them, established by the field, highlighting well-worn paths, pointing out pitfalls, and noting where few have yet to trod. Contributing to this cartography, we consider ethical questions encountered during development and production of three RbT projects involving family members who have passed: Homa Bay Memories, Brothers, and Unload . In doing so, we question which stories might be best left untold and the evolution of relationships throughout the research. Exploring these together helps to develop a landscape of ethical possibilities and establish guideposts to help illuminate challenges for future RbT projects.